A microRNA‐1 gene, tci‐miR‐1‐3p, is involved in cyflumetofen resistance by targeting a glutathione S‐transferase gene, TCGSTM4, in Tetranychus cinnabarinus. Issue 3 (8th February 2018) - Zhang, Y.; Feng, K.; Hu, J.; Shi, L.; Wei, P.; Xu, Z.; Shen, G.; Li, M.; Xu, Q.; He, L.
Abstract: microRNA‐1 ( miR‐1 ) is a well‐studied conservative microRNA (miRNA) involved in immune responses in mammals and insects. However, little is known about its role in pesticide resistance in arthropods. In this study, we found that a microRNA belong to miR‐1 family ( tci‐miR‐1‐3p ) was significantly down‐regulated in a cyflumetofen‐resistant strain (CYR) of Tetranychus cinnabarinus compared with its homologous susceptible strain (SS), indicating an involvement of miR‐1 in cyflumetofen resistance in mites. One glutathione S‐transferase (GST) gene ( TCGSTM4, a mu class GST gene), a candidate target gene of tci‐miR‐1‐3p, was found to be significantly down‐regulated when tci‐miR‐1‐3p was over‐expressed. The specific interaction between tci‐miR‐1‐3p and the target sequence in the 3′ untranslated region of TCGSTM4 was confirmed. A decrease or increase in tci‐miR‐1‐3p abundance through feeding miRNA inhibitors or mimics significantly increased or decreased TCGSTM4 expressions at the mRNA and protein levels, respectively. In addition, an over‐expression of tci‐miR‐1‐3p resulted in a decrease in the tolerance of T. cinnabarinus to cyflumetofen in both SS and CYR strains, and vice versa. After decreasing TCGSTM4 transcription via RNA interference, T. cinnabarinus became more sensitive to cyflumetofen in both resistant and susceptible mites, and the change in mortality was greater in CYR than that in SS. Moreover, the recombinant TCGSTM4 could significantly decompose cyflumetofen, indicating that TCGSTM4 is a functional gene responsible for cyflumetofen resistance in mites.